2005
DOI: 10.1207/s15327655jchn2203_1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Osteoporosis Knowledge: A Community Study

Abstract: According to the 2004 Surgeon General's report, more than 10 million people in the United States have osteoporosis, and another 34 million are at risk of developing this crippling disease that affects the quality of life. Efforts must be made to stem this disease that may be largely prevented with lifestyle changes. To engage in self-care to prevent osteoporosis, people need to have knowledge of risks and preventive behaviors. The purpose of this study was to examine factors influencing osteoporosis knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Other Study show that women aged (50-59) year have increased incidence of osteoporosis (10). Study reported that18 million woman have low bone mass and risk for osteoporosis , half of them aged 50 years and older will have at least one osteoporosis-related fracture in their lifetime (11). Regarded marital status the highest percentage (65%) of the study sample were married as shown in Table (1).Higher risk for low bone mineral density among married women, marriage is associated with pregnancy and breastfeeding of the newborns which are both factors that decrease the bone mineral density Therefore, a higher risk of osteoporosis among married women compared with women who are single (12 , 13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Other Study show that women aged (50-59) year have increased incidence of osteoporosis (10). Study reported that18 million woman have low bone mass and risk for osteoporosis , half of them aged 50 years and older will have at least one osteoporosis-related fracture in their lifetime (11). Regarded marital status the highest percentage (65%) of the study sample were married as shown in Table (1).Higher risk for low bone mineral density among married women, marriage is associated with pregnancy and breastfeeding of the newborns which are both factors that decrease the bone mineral density Therefore, a higher risk of osteoporosis among married women compared with women who are single (12 , 13,14).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Knowledge and calcium intake was also found to be weakly associated, indicating that disease knowledge has little influence and calcium intake. The low knowledge level of the population justifies the need for more osteoporosis education targeted to young adult women, especially in the areas of risk factor, prevention, and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,18 Despite the various sources available providing osteoporosis information to women of various ages, studies have shown that knowledge levels about the disease are consistently low. [16][17][18][19][20] Calcium intake among women in the United …”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the participants had inadequate knowledge about osteoporosis. 5 In Turkey, a study was done to determine knowledge, attitude and prevention of osteoporosis among 311 women, using a self-administered questionnaire, which revealed that 60% of women were unaware of osteoporosis and 40% were unable to identify significant risk factors. The results of the study were, 75% of women had inadequate knowledge of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%